Vistas in geological research. - Acharya, S. (Satyananda); Utkal University. P.G. Department of Geology (Bhubaneswar : P.G. Dept. of Geology, Utkal University, 1995)
Contributed articles chiefly on Orissa, India.
"Prof. S. Acharya felicitation volume."
Includes bibliographical references and index.
Keywords: Geology -- India -- Orissa Region; Minerals -- India -- Orissa Region